Review of major meat-borne zoonotic bacterial pathogens - Ali, Sultan; Alsayeqh, Abdullah F. (Frontiers in Public Health, 2022)
Meat-borne pathogens are of great public health significance due to food safety and causing disease worldwide. These pathogens can cause gastrointestinal diseases due to the consumption of contaminated vegetative pathogens or their toxins. Bacterial meat-borne pathogens are responsible for a variety of different human diseases with the majority of infections occurring in developing countries. The objective of this review is to highlight the meat-borne bacterial zoonotic pathogen keeping in view One Health's perspective. Meat and meat products can be contaminated with pathogens or with their toxins during various steps of production, processing, transportation, and food preparation. E. coli, Salmonella, Listeria monocytogenes, Shigella, Campylobacter, Brucella, Mycobacterium bovis, and toxins produced by Staphylococcus aureus, Clostridium species, and Bacillus cereus are responsible for meat borne illnesses worldwide. These zoonotic bacterial pathogens are mainly attributed to diseases related to the gastrointestinal system. Consumption of meat or meat products with multidrug-resistant bacteria is of great concern for public health. The control of these bacterial pathogens can be achieved by controlling these pathogens at the human, animal, and environmental interface.